Flow in vortex diodes - Pandare, Aditya; Ranade, Vivek V. (Chemical Engineering Research & Design, 2015)
A vortex diode is used as a cavitation device for treatment of industrial waste water and also, as a leaky non-return valve in nuclear applications. It consists of a vortex chamber with an axial and tangential port. When the fluid is injected through the tangential port, a strong vortex flow is set up in the diode chamber. This flow is characterized by phenomena such as vortex transition, precessing vortex core, toroidal recirculation zone, reverse flow core and recirculation zone in the axial port. Although studies have been conducted on the ``confined vortex'' class of flows (and some of them on vortex diodes), none of them provides a collective account of key nuances of the flow in a vortex diode. The flow in the diode differs from other confined-vortex flows on account of the axial-velocity deficit, due to which, direct correlations from other confined vortex flows cannot be applied to the diode. This work attempts to address the aforementioned flow characteristics in the diode using results primarily from CFD simulations. The reported methodology, computational model and results will be useful to gain better understanding of flows in vortex diodes and to optimize designs of vortex diodes for variety of applications. (C) 2015 Published by Elsevier B.V. on behalf of The Institution of Chemical Engineers.
Keywords: CFD; Confined vortex; Diode; Precessing vortex core; Recirculation